Pendampingan Pengurusan Sertifikasi Halal Pada Dua UMKM Produk Olahan Mie di Kecamatan Bangsalsari Jember - Mutmainah, Siti; Purnani, Siwi Tri; Hasanah, Dina Fitria; Azizah, Hilma Azmi (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
Currently, the sustainability of MSMEs businesses in the food sector depends on the halal status of the products. This phenomenon is in accordance with the establishment of halal certification. A strict halal certification system has been implemented to ensure that food and beverage products meet the halal standards regulated by the government. The lack of access to information and limited knowledge caused the businessmen of MSMEs getting difficulties to obtain halal certification. This community service activity aims to provide socialization and assistance to both service partners, Mie Ayam Ruham and D’Jaguar Food, in obtaining halal certification for their flagship products. Mie Ayam Ruham has chicken noodle as its flagship product, while D’Jaguar Food has mie galak as its flagship product. Both partners are located in Bangsalsari District, Jember Regency. The community service activities are divided into several stages: preparation stage, halal assurance system socialization stage, interviews and discussions, technical assistance, and preparation of halal certification document requirements. Both service partners provided positive feedback on these community service activities. The technical assistance process and document preparation assistance were supposed to convey simple understanding of the importance of halal certification, facilitate the work, and provide clear understanding to both partners.